FOMO, Ephemerality, and Online Social Interactions among Young People. Issue 4 (1st December 2018) - Park, Sora
Abstract: Among young people's online activities, a significant portion involves social networking and communication. The additional social space afforded by the Internet has extended the way young people relate to their surrounding world. This study examined how young people adapt to the networked digital space. Semistructured interviews with adolescents (twelve to eighteen years old) in South Korea and Australia revealed that new norms of social interaction are constantly created and negotiated. First, online participants carefully curate what can be seen and what should be hidden from others. Knowing the global and permanent nature of digital traces, users are mindful of what they post and how they interact online. Second, the continuous presence online results in rapid cycles of interactions, pressuring network members to respond immediately. Online interactions are quickly replaced by new ones, creating a sense of ephemerality. Third, there is a close tethering of the online to the offline world. Young people constantly engage in multiple and simultaneous online social interactions while dipping in and out of their physical realities. The tension between permanency and ephemerality leads online participants to question the authenticity of the partial reality that is depicted online and adds complexity to the norms of social interaction. Fear of missing out (FOMO) existed in both groups of adolescents and was reflected in how frequently they engaged in online interactions.